Designing Factory Layout and Facilities for Car Front Door Production with CORELAP: A Case Study at PT GMI - Purwojatmiko, B. Handoko; Sumasto, Fredy; Ahmad, Takbir Dhuha Shaffah; Hastin, Shafira Fitriani (Performa: Media Ilmiah Teknik Industri, 2025)
The automotive manufacturing industry is experiencing significant development and has increasingly complex market demand dynamics. The industrial transformation resulting from these developments has had a significant impact on several automotive manufacturing companies. The value of production efficiency, on-time delivery, and product quality means that companies must have the right strategy in meeting customer demand. Fulfilling customer requests can be realized by opening new adequate facilities. Factory layout and facility design can be a key factor in achieving this goal, especially in the production of front door components model. This research aims to comprehensively detail the design of the factory layout and facilities using the CORELAP method. CORELAP implementation involves collecting supporting data, including Operation Process Chart (OPC), Routing Sheet, Floor Area Requirement, Activity Relationship Chart (ARC), and Activity Relationship Diagram (ARD). The CORELAP method prioritizes spatial relationships to ensure that closely related facilities are strategically located. Design This layout design was created to provide an overview of the strategy for structuring production facilities and their supports to produce an effective and efficient design. Apart from the overview, the analysis carried out can also provide space for stakeholders to be able to utilize the CORELAP strategy in creating new factory layouts and facilities to support improving the company's work performance and meet customer satisfaction. The cost of material handling is calculated to determine the expenses involved in establishing a production facility for car front doors, totaling IDR 763,959. This cost is approximately 10% lower than the current material handling cost, which is IDR 856,888. The results of this research are design proposals that can be utilized or taken into consideration by industrial stakeholders.